The Effect of Work-Life Balance and Job Stress on Employee Performance at PT. Adyawinsa Plastic Industry, Bekasi Regency, Using Employment Status as a Moderating Variable - Marisa Angelica; Saidun Hutasuhut (Economic: Journal Economic and Business, 2025)
This research is motivated by the importance of work life balance and job stress in determining employee performance. The purpose of the study is to determine the effect of work life balance and job stress on employee performance with work status as a moderating variable at PT. Adyawinsa Plastic Industry, Bekasi Regency. The research method uses a quantitative approach with a survey technique through a questionnaire to 91 permanent and contract employee respondents. Data analysis was carried out with Smart-PLS to test the validity, reliability, and influence between variables. The results of the study indicate that: (1) work life balance has a positive and significant effect on employee performance, (2) work stress has a negative and significant effect on employee performance, (3) work status is unable to moderate the effect of work life balance on employee performance, and (4) work status can moderate the effect of work stress on employee performance. The conclusion shows that work life balance has a positive and significant effect on employee performance, as well as work stress has a negative and significant effect on employee performance. Work status cannot moderate the relationship between work life balance and employee performance, but is able to moderate the effect of work stress on employee performance.